(untitled) (Vietnam Journal of Community Medicine, 2024)
Advanced non-small cell lung cancer (NSCLC) with EGFR (Epidermal Growth Factor Receptor) mutations shows high efficacy with EGFR TKIs (Tyrosine Kinase Inhibitors) in terms of progression-free survival (PFS) and disease control rate (DCR) compared to standard chemotherapy. Objective: To evaluate the response rate of afatinib in first-line treatment for advanced NSCLC (stage IIIC, IV) with EGFR mutations and its adverse effects. Methods: A retrospective descriptive study of 16 patients with advanced non-small cell lung cancer with EGFR mutations treated with afatinib as first-line therapy at Thong Nhat Hospital from January 1, 2018 to July 31, 2022. Results: The average age was 66 years (66.06 ± 12.81), with the oldest patient being 88 years old and the youngest being 45 years old. Female patients accounted for a higher percentage compared to male patients, with rates of 75% and 25%, respectively. The complete response (CR) rate was 12.5%, partial response (PR) was 50%, stable disease (SD) was 31.3%, and progressive disease (PD) was 6.3%. The disease control rate (DCR) was 93.8%, with a median PFS of 23 months and a median overall survival (OS) of 38 months. Common adverse effects included rash (100%), diarrhea (93.8%), paronychia (87.5%), and stomatitis (87.5%). No grade 3 or 4 adverse effects were observed. Conclusion: Afatinib provides a high response rate in patients with advanced non-small cell lung cancer with EGFR mutations sensitive to TKIs. Adverse effects can be controlled.